Pengolahan Makanan Berbasis Potensi Desa sebagai Sumber Ekonomi Kreatif Masyarakat - Mega Tunjung Hapsari (Universitas Lancang Kuning, 2021)
The abundant natural potential in the southern tip of Blitar Regency, East Java Province is not directly proportional to the ability of village communities to manage so that natural products sold at prices below market standards. A mediocre economy makes the group of mothers who are members of the Empowerment of Family Welfare try to get additional income. This dedication has succeeded in realizing the community empowerment program through training on village-based food processing, that is the avocado fruit, as a source of creative economy for the village community. Community service activities are carried out using the ABCD (Asset Based Community Development) method through four steps, namely: 1) Observation; 2) Planning; 3) Implementation; and 4) Evaluation. The results of the community service activities are the creative idea of ​​food processing and aspects of food production. Now village communities, especially housewive, are more creative and empowered and can generate additional income to help the family economy.